Incidence of the third head of biceps brachii in population of Andhra Pradesh - Vishal Manoharrao Salve; Chandaka Swathi Poornima; Mandava Prabhakar Rao (Wolters Kluwer Medknow Publications, 2013)
Background and aims: The biceps brachii is a large fusiform muscle in the flexor compartment of the arm. In terms of the number and morphology of its head, the biceps brachii muscle is one of the most variable muscles in human body. The present study explores the importance of such variations. Materials and methods: The upper limbs of embalmed human cadavers (fixed in 10 % formaldehyde solution) were included in present study. Total 36 (72 upper limbs) cadavers were studied by dissection. Results: Among the 72 superior extremities studied, six (8.33%) arms were found to have a three- headed biceps brachii muscles. The variation was present in the left arm of four males and one female. The variation was present in the right arm of one male. Conclusion: Presence of third head of biceps brachii muscle might increase its kinematics. Supernumerary heads of biceps brachii muscle may become significant in pre-operative procedure and during surgery of upper limb.